2021
DOI: 10.1002/eco.2393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roots systems on hydrological connectivity below the soil surface in the Yellow River Delta wetland

Abstract: In this study, a new method based on field dye-tracing experiments was used to assess hydrological connectivity below the soil surface. In this method, Phragmites australis in the Yellow River Delta wetland was considered to characterize the interaction between roots systems and hydrological connectivity. The results showed that index of hydrological connectivity (IHC) declined non-linearly with depth below the soil surface. Roots systems of P. australis were mostly distributed in soils of 0-30 cm.Roots system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…The DC is defined as the ratio of the dye-stained area to the total area of the vertical profile [19].…”
Section: Field Dye-tracing Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DC is defined as the ratio of the dye-stained area to the total area of the vertical profile [19].…”
Section: Field Dye-tracing Experimentsmentioning
confidence: 99%
“…The fractal dimension (FD) of the dye image reflects the complexity of the wetting front of the soil water movement [34]. Even when the stained regions are The DC is defined as the ratio of the dye-stained area to the total area of the vertical profile [19].…”
Section: Ihc Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface soil is also rich in root systems (Table 1) (Zhang et al, 2017; Zhang, Niu, Yu, et al, 2015; Zhang, Niu, Zhu, et al, 2015). Previous studies indicated that pores between root systems and the surrounding soils can interconnect with decayed root channels (Zhang et al, 2018; Zhang et al, 2022). The interconnected pores networks can promote solute transport.…”
Section: Discussionmentioning
confidence: 99%
“…Soil column dye staining patterns at soil depths at the tree site (a) and the bush site (b) . Previous studies indicated that pores between root systems and the surrounding soils can interconnect with decayed root channels (Zhang et al, 2018;Zhang et al, 2022). The interconnected pores networks can promote solute transport.…”
Section: Steady Infiltration and Effluents Concentration Changesmentioning
confidence: 99%